The Influence of Work Motivation and Work Discipline on Employee Performance Manado Independent School - Soewignyo, Tonny; Paat, Silvia Friska; Kainde, Llly Linne; Mandagi, Deske Wenske; Petir, Abraham Leslie; Rantung, Rinny Cherryl (Syntax Literate, 2024)
This research aims to investigate the influence of motivation and discipline on employee performance at Manado Independent School. Utilize quantitative research methods to determine whether motivation and discipline have an impact on employee performance. Primary data sources were used for this study. The data analysis method employed was multiple linear regression analysis conducted using SPSS 26 software. Data collection was carried out by distributing questionnaires to 100 respondents. Overall, the results of the multiple linear regression analysis and hypothesis testing suggest that motivation and discipline have a positive and significant influence when considered simultaneously, with a p-value of 0.000 < 0.05. The coefficient value is 1.87, and the adjusted R-squared value is 76.31%. Consequently, it can be concluded from this study that, partially, the variable of work motivation does not have a significant influence on employee performance, whereas the variable of work discipline has a significant impact on employee performance productivity. Therefore, efforts should be made to enhance work motivation to positively impact employee performance.